A web of opportunity or the same old story? Women digital entrepreneurs and intersectionality theory - Martinez Dy, Angela Carmina; Marlow, Susan; Martin, Lee (Sage Publications, 2016)
This article critically analyses the manner in which intersectionality and related social positionality shape digital enterprise activities. Despite popular claims of meritocratic opportunity enactment within traditional forms of entrepreneurship, ascribed social characteristics intersect to influence the realisation of entrepreneurial potential. However, it is purported that the emerging field of digital entrepreneurship may act as a ‘great leveller’ due to perceived lower barriers to entry, disembodiment of the entrepreneurial actor and the absence of visible markers of disadvantage online. Using an interpretivist approach, we analyse empirical evidence from UK women digital entrepreneurs which reveals how the privileges and disadvantages arising from intersecting social positions of gender, race and class status are reproduced online. This analysis challenges the notion that the Internet is a neutral platform for entrepreneurship and supports our thesis that offline inequality, in the form of marked bodies, social positionality and associated resource constraints, is produced and reproduced in the online environment.